Late presentation of distal biceps brachii tendon rupture in a collegiate cricket player treated with peroneus longus interposition graft augmented repair – a case report - Somasundaram, Anand K.; Sreeja, Aiswarya A.; Appukuttan, Anjali (International Journal of Research in Orthopaedics, 2025)
The incidence of distal biceps brachii tendon rupture in athletes is a rare condition with an incidence of 1.2 – 2.55 cases per 100,000 patients per year. The injury mechanism often involves an eccentric load on a flexed, supinated elbow. Most commonly, these injuries occur in strength athletes and in those involved in contact sports such as American football and rugby. The additional risk factors include smoking, anabolic steroid use and obesity. Distal biceps brachii tendon rupture is a very rare injury in cricket players which has not been reported in the published literature. A delayed presentation of such an injury is even more rare and a challenge to the treating physician. A club-level cricket player in his late thirties presented 3 months after an injury to his left elbow while playing a match. His complaints were pain and inability to play the cricketing drive shots. On clinical examination he had good power of isolated elbow flexion with poor grades of power of supination of his forearm in a flexed elbow position. The distal biceps brachii tendon was not palpable in a hook test with mild swelling of his arm with a ‘popeye’ bulge on attempted elbow flexion. He was diagnosed to have a distal biceps brachii tendon rupture and was managed with surgical repair incorporating an autologous peroneus longus tendon as an interposition graft. At six months follow-up he was completely recovered and back to playing cricket. This case signifies the importance of diagnosing a rare cricketing injury. A detailed surgical plan which essentially involved confirming the site of rupture of the tendon, planning for an interpositional tendon augmentation in view of the retracted, immobile tendon ends and a tailored rehabilitation program was instrumental in yielding a successful outcome.